The biology, damage and within-tree distribution on the spruce bud midge on black spruce in Newfoundland - West, R. (Phytoprotection, 1990)
The spruce bud midge (Rhabdophaga swainei) has one generation a year on black spruce (Picea mariana) in Newfoundland. Newly hatched larvae enter primordia of flushing buds in late June and early July and larvae mature by fall to overwinter within buds. Pupation occurs within buds the following spring and adults emerge in June. Virgin females averaged 86 eggs upon dissection. Platygaster rhabdophagae, Mesopolobus sp., Torymus sp., and Tetrastichus sp. were responsible for high parasitism levels of spruce bud midge larvae. Terminal buds were attacked significantly more than lateral or uppermost lateral buds. The number of infested buds was significantly higher in the top third of the crown than in the bottom crown third, but was not significantly different among north, east, south and west crown exposures. The apical meristem never developed in infested buds, and these buds did not flush. The growth of bud primordial cells is redirected by R. swainei to produce gall tissues that provide nutrients and an overwintering shelter for the larva. Attack of the terminal leader causes a slight loss in height growth but normal leader growth resumes the following year.